2003
DOI: 10.1093/qjmed/hcg157
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for thiazide-induced hyponatraemia

Abstract: Hyponatraemia is a common problem after thiazide therapy. Extra caution and close monitoring are warranted when prescribing thiazides for elderly patients with low body mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
4
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 43 publications
6
109
4
2
Order By: Relevance
“…16 Serum uric acid levels, which typically rise with volume depletion, were lower in patients with thiazide-induced hyponatremia as compared with normonatremic patients taking thiazides. 15 Taken together, these data suggest a role for abnormal thirst and water intake in individuals who develop thiazide-induced hyponatremia.…”
Section: S4mentioning
confidence: 81%
See 1 more Smart Citation
“…16 Serum uric acid levels, which typically rise with volume depletion, were lower in patients with thiazide-induced hyponatremia as compared with normonatremic patients taking thiazides. 15 Taken together, these data suggest a role for abnormal thirst and water intake in individuals who develop thiazide-induced hyponatremia.…”
Section: S4mentioning
confidence: 81%
“…14 Although most patients with diuretic-induced hyponatremia are women, whether female sex or lower body weight confers increased risk is uncertain. 15 Patients with a prior episode of thiazide-induced hyponatremia demonstrate increased susceptibility to a recurrence. When compared with both elderly and young controls, patients with a prior history had lower basal urine osmolality and demonstrated a greater decrease in serum [Na ϩ ] after rechallenge with a single dose of diuretics.…”
Section: S4mentioning
confidence: 99%
“…23 However, this study did not adjust for the confounding effect of concomitant medications and other reported risk factors like weight, renal function etc. 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] The elderly appear to be more prone to TIH as they do not excrete free water as efficiently as younger subjects. 9 Blunted prostaglandin synthesis may contribute, along with polypharmacy, particularly including nonsteroidal anti-inflammatory agents.…”
Section: Epidemiologymentioning
confidence: 99%